Improving the Efficiency of IMS–IMS by a Combing Technique - Merenbloom, Samuel I. (2008)
A simple method for increasing the efficiency of multidimensional ion mobility spectrometry (IMS–IMS) measurements (as defined by the number of two-dimensional data sets necessary to sample all of the ions in a complex mixture) is illustrated. In this approach, components from a packet containing a mixture of ions are introduced into the first IMS drift region where they are separated based on differences in mobility. At the exit of this region, narrow distributions of ions having identical mobilities are selected, subjected to gentle activation conditions that are intended to induce conformational changes, and transmitted into a second IMS drift region where the new conformations are separated. Here, we describe a simple timing sequence associated with selection and activation of multiple distributions at the entrance of the second drift region in a systematic fashion that improves the efficiency of two-dimensional IMS–IMS by a factor of ~8. The method is illustrated by examination of a mixture of tryptic peptides from human hemoglobin.